Perlindungan Perempuan Dan Anak Dalam Merehabilitasi Korban Tindak Pidana Kekerasan Seksual Melalui Media Online - Fitria Sari, Cucun Cundaya; Ira Ghina Salsabila; Suwari Akhmaddhian; Dikha Anugrah (Fakultas Hukum Universitas Mulawarman, 2025)
ABSTRACT The development of digital technology has both positive and negative impacts on society. One of the most common negative impacts is sexual violence, targeting women and children as the primary victims. The Women and Children Protection Unit plays a crucial role in the rehabilitation process for victims of sexual violence. The purpose of this study was to determine how the Women and Children Protection Unit's authority is regulated in rehabilitating victims of sexual violence through online media and how the Women and Children Protection Unit's authority is implemented in rehabilitating victims of sexual violence through online media. The research method used was an empirical juridical approach with data collection through observation, interviews, and literature studies. The results of the study indicate that the Women and Children Protection Unit's authority is regulated in Article 14 of Law Number 2 of 2002 concerning the Indonesian National Police and Article 4 of the Indonesian National Police Regulation Number 10 of 2007 concerning the Organization and Work Procedures of the Women and Children Service Unit (PPA Unit) within the Indonesian National Police. In exercising its authority, the Women and Children Protection Unit of the Kuningan and Cirebon Police Departments coordinates with relevant agencies involved in the protection of women and children. However, victim rehabilitation remains hampered by challenges such as limited facilities, public stigma, and minimal reporting, particularly in online-based cases. Therefore, strengthening technical regulations specifically governing procedures for handling online-based sexual violence is necessary, particularly regarding digital evidence and guaranteeing victims' rights. Local governments should also provide rehabilitation infrastructure, such as safe houses, child psychological services, and PPA Unit officers specifically trained to handle online-based sexual violence. They should also improve legal and digital literacy through legal education in schools and public campaigns to ensure victims are not afraid to report and to ensure the public understands the risks of digital interactions. ABSTRAK Perkembangan teknologi digital memberikan dampak positif dan negatif bagi masyarakat. Salah satu dampak negatif yang marak terjadi adalah kekerasan seksual yang menyasar perempuan dan anak sebagai korban utama. Unit Perlindungan Perempuan dan Anak berperan penting dalam proses rehabilitasi korban kekerasan seksual. Tujuan dari penelitian ini untuk mengetahui bagaimana pengaturan Kewenangan Unit Perlindungan Perempuan dan Anak dalam merehabilitasi korban tindak pidana kekerasan seksual melalui media online dan bagaimana penerapan Kewenangan Unit Perlindungan Perempuan dan Anak dalam merehabilitasi korban tindak pidana kekerasan seksual melalui media online. Metode penelitian yang digunakan dengan pendekatan yuridis empiris dengan pengumpulan data melalui observasi, wawancara, dan studi kepustakaan. Hasil penelitian menunjukkan bahwa kewenangan Unit Perlindungan Perempuan dan Anak diatur dalam Pasal 14 Undang-Undang Nomor 2 Tahun 2002 tentang Kepolisian Negara Republik Indonesia dan Pasal 4 Peraturan Kepolisian Negara Republik Indonesia Nomor 10 Tahun 2007 tentang Organisasi dan Tata Kerja Unit Pelayanan Perempuan dan Anak (Unit PPA) di Lingkungan Polri. Dalam menerapkan kewenangannya, Unit PPA Kepolisian resor Kuningan dan Cirebon melakukan koordinasi dengan instansi terkait yang berhubungan dengan perlindungan perempuan dan anak, namun rehabilitasi korban masih terkendala, seperti fasilitas yang terbatas, stigma masyarakat, dan minimnya pelaporan, terutama pada kasus berbasis online. Oleh karena itu, perlu adanya penguatan regulasi teknis yang secara spesifik mengatur prosedur penanganan kekerasan seksual berbasis online, terutama dalam hal pembuktian digital dan jaminan hak korban, serta pemerintah daerah perlu menyediakan infrastruktur rehabilitasi, seperti rumah aman, layanan psikologis anak, serta petugas Unit PPA yang terlatih khusus menangani kekerasan seksual berbasis media online, meningkatkan literasi hukum dan digital masyarakat melalui pendidikan hukum di sekolah dan kampanye publik agar korban tidak takut melapor dan masyarakat memahami risiko interaksi digital.